Strategic study of total innovation management and its relationship with marketing capabilities in palm conversion and complementary industries - Neda Baniasadi; Davoud Samari; Seyyed Jamal Farajollah Hosseini; Maryam Omidi Najafabadi (Journal of Innovation and Entrepreneurship, 2021)
Given the role and importance of processing and complementary industries in preventing waste from agricultural products, the establishment of such industries can be considered as one of the most appropriate solutions for agricultural development. For this purpose, the data were collected for data processing and complementary industries in the fields of packing, pricing, customer orientation, in south of Iran. Method: According to the goals and assumptions, descriptive-analytical research and its survey method is a survey. According to the Cochran formula, 155 people are involved in marketing, packaging and processing of palm in Kerman province. To answer the research questions, SPSS software and AMOS software were used to analyze the results. Findings "Indigenous Knowledge in packing". Using communication tools in marketing impact of customer-orientation approach are Top Priorities in "marketing Date". The "packaging" factor is the most important factor in the marketing development of date conversion and complementary industries.
Keywords: 650; Total innovation management; Conversion and complementary industries; Date; Marketing; Agri-food system